Alterations in mucosal structures and key regulatory molecules of oxidative stress in Atlantic salmon (Salmo salar L.) induced by amoebic gill disease and oxidant-based chemotherapeutic interventions - Furtado, Francisco Machado Faria (2022)
Dissertação de Mestrado Integrado em Medicina Veterinária